Hippophae Linn. (Seabuckthorn) in India: a Review - Naithani, H. B. (Indian Forester, 2004)
Seabuckthorn (Hippophae spp.) belongs to family Elaeagnaceae. It grows in the forest areas of Mountains from Hindu Kush - Himalayan region , adjoining area's of China and parts of Europe. There are three species of genus Hippophae distributed in the Himalayan part of India. Seabuckthorn forests are supposed to be a store house of nutrients and many items like jams , soft drinks , sauces , pickle , jelly and biscuits are made from it. Its fruits are good source of vitamins. Apart from this , it is used as firewood , fencing soil conservation. In India , the Field Research Laboratory , Leh has developed few products from it like Jam , squash , sauces , pickles etc. Squash produced by them does not freeze up to -22Â°C. Suitable products from Hippophae salicifolia can raise the economic status of the people of Uttaranchal.